2011
DOI: 10.1088/0004-637x/740/2/105
|View full text |Cite
|
Sign up to set email alerts
|

Is SGR 0418+5729 Indeed a Waning Magnetar?

Abstract: SGR 0418+5729 is a transient soft gamma-ray repeater which underwent a major outburst in 2009 June, during which the emission of short bursts was observed. Its properties appeared quite typical of other sources of the same class until long-term X-ray monitoring failed to detect any period derivative. The present upper limit onṖ implies that the surface dipole field is B p 7.5 × 10 12 G, well below those measured in other soft gamma-ray repeaters (SGRs) and in the Anomalous X-ray Pulsars (AXPs), a group of simi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(118 citation statements)
references
References 44 publications
6
110
0
2
Order By: Relevance
“…As argued in more detail in Rea et al (2012), we note that the discovery of a second magnetar-like source with a magnetic field in the radio-pulsar range strengthens the idea that magnetar-like behavior may be much more widespread than what believed in the past, and that it is related to the intensity and topology of the internal and surface toroidal components, rather than only to the surface dipolar field (Rea et al 2010, Perna & Pons 2011, Turolla et al 2011.…”
Section: Discussionsupporting
confidence: 74%
“…As argued in more detail in Rea et al (2012), we note that the discovery of a second magnetar-like source with a magnetic field in the radio-pulsar range strengthens the idea that magnetar-like behavior may be much more widespread than what believed in the past, and that it is related to the intensity and topology of the internal and surface toroidal components, rather than only to the surface dipolar field (Rea et al 2010, Perna & Pons 2011, Turolla et al 2011.…”
Section: Discussionsupporting
confidence: 74%
“…∼ 6 × 10 12 G; Rea et al 2013). Simulations of magnetic field evolution in neutron stars with different initial field strength and configuration have shown that, a relatively old magnetar such as SGR 0418+5729 despite its low surface dipolar field, might still harbor a sufficiently intense internal/crustal toroidal field to give rise to outbursts and short X-ray bursts (Turolla et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The decay rate of the dipole field depends mainly on the strength of the initial crustal toroidal arXiv:1412.1677v2 [astro-ph.HE] 11 Jan 2015 field. For instance, for a neutron star to reach the properties of the so-called low-B magnetar SGR 0418+5729, it should have an initial toroidal field stronger than 10 16 G (Turolla et al 2011). For a second low-B magnetar Swift J1822.3-1606, the model needs an initial crustal toroidal field with a strength of a few 10 14 G.…”
Section: Introductionmentioning
confidence: 99%